ECO-PERSPECTIVAS EN EDUCACIÓN AMBIENTAL - Valencia Vargas, Steiner (Tecné, Episteme y Didaxis: TED, 2017)
This proyect assumes that people’s opinions and images of knowledge, reality and living things, determine the formulation, design and implementation of educational proposals regarding environmental issues. There fore, the analysis and the making of these images explicit are considered fundamental to build conceptual perspectives that structure pedagogical practices about environmental issued. Conceptual perspectives that make posible as conscious and deliberate pedagogical practice, this should contribuite to the cultural transformation of the contexts where they are developed.